The Effect of Modern Techonology on Traditonal Architectural Expression: Case of Old Calabar Architecture (Global Journal of Science Frontier Research, 2015)
Recently, there has been serious concern expressed over the fact that traditional architecture's language, its system of representation and indeed, its technology are excluded from the industrial future and hence from training, due to modern technology. Consequent upon this, the immense capital know -how held by building -related craft-trades, is disparaged as a pre-industrial and historical phenomenon and, as such banned from technical training and economic practice and retained merely as a subject for archaeology and arts and craft history courses. Thus, we are faced with a scandalous reduction in the productive capacities of society as a whole and with the radical impoverishment of basic democratic choices relating to vocations and trades and, generally, with the means of human self -expression. This study, therefore, seeks to establish the authenticity or otherwise of these allegations against modern technology. In doing this, a careful study was made of the developments in architecture with respect to its historical antecedents, specifically from the pre-World War 2 to the modern architectural era, 1945 till date.
Keywords: modern technology; art; traditional architecture; architectural expression; old calabar